Home /
Expert Answers /
Advanced Math /
solve-using-laplace-transform-formulas-i-included-an-attachment-of-the-laplace-transform-tables-2-pa317
(Solved): SOLVE USING LAPLACE TRANSFORM FORMULAS. I included an attachment of the laplace transform tables 2. ...
SOLVE USING LAPLACE TRANSFORM FORMULAS. I included an attachment of the laplace transform tables
2. Solve the initial value problem 4y??+y=U(t??),y(0)=1,y?(0)=0 Note: The angle addition formulas on page 8 of the additional formulas sheet may be useful.]
4. Solve the initial value problem y??2y=g(t),y(0)=1 given g(t)={et2?0?t<33?t?
Given f(t), F(s)=L{f(t)}=?0??e?stf(t)dt for all value of s for which the improper integral converges. In the tables below, let G(s)=L{g(t)},H(s)=L{h(t)}. (1) f(t)=1,F(s)=s1? (2) f(t)=t,F(s)=s21? (3) f(t)=n!tn?,F(s)=sn+11?(n=0,1,2,?)? (4) f(t)=cg(t/c)?,F(s)=G(cs) (5) f(t)=?t?1?,F(s)=s?1? (6) f(t)=(1?3?5?(2n?1)??)2ntn?21??,F(s)=s?(n+21?)(n=0,1,2,?)? (7) f(t)=tq?1,F(s)=sq?(q)?(q>0) (8) f(t)=eat,F(s)=s?a1?
(9) f(t)=teat,F(s)=(s?a)21? (10) f(t)=n!tneat?,F(s)=(s?a)n+11?(n=0,1,2,?)? (11) f(t)=a?beat?ebt?,F(s)=(s?a)(s?b)1?(a?=b) (12) f(t)=a?baeat?bebt?,F(s)=(s?a)(s?b)s?(a?=b)? (13) f(t)=?(a?b)(b?c)(c?a)(b?c)eat+(c?a)ebt+(a?b)ect?,F(s)=(s?a)(s?b)(s?c)1?,(a?=b?=c?=a)? (14) f(t)=?(a?b)(b?c)(c?a)a(b?c)eat+b(c?a)ebt+c(a?b)ect?,F(s)=(s?a)(s?b)(s?c)s?(a?=b?=c?=a)? (15) f(t)=?(a?b)(b?c)(c?a)a2(b?c)eat+b2(c?a)eht+c2(a?b)ed?,F(s)=(s?a)(s?b)(s?c)s2?(a?=b?=c?=a)? (16) f(t)=sinat,F(s)=s2+a2a?
(17) f(t)=cosat,F(s)=s2+a2s?(18)f(t)=sin(at+b),F(s)=s2+a2ssinb+acosb? (19) f(t)=cos(at+b),F(s)=s2+a2scosb?asinb?(20)f(t)= sinhat, F(s)=s2?a2a?f(t)=coshat,F(s)=s2?a2s?f(t)=a21?cosat?,F(s)=s(s2+a2)1? (23) f(t)=a3at?sinat?,F(s)=s2(s2+a2)1?(24)f(t)=2a3sinat?atcosat?,F(s)=(s2+a2)21?(25)f(t)=2atsinat?,F(s)=(s2+a2)2s?(26)f(t)=2asinat+atcosat?,F(s)=(s2+a2)2s2?f(t)=tcosat,F(s)=(s2+a2)2s2?a2?
(28) f(t)=b2?a2(1/a)sinat?(1/b)sinbt?,F(s)=(s2+a2)(s2+b2)1? (29) f(t)=b2?a2cosat?cosbt?,F(s)=(s2+a2)(s2+b2)s?(a2?=b2)?(30)f(t)=eatsinbt,F(s)=(s?a)2+b2b?(31)f(t)=eatcosbt,F(s)=(s?a)2+b2s?a?(32)f(t)=eat(cosbt+ba?sinbt),F(s)=(s?a)2+b2s? (33) f(t)=a2+b2aeatsinbt?beatcosbt+b?,F(s)=s((s?a)2+b2)b?(34)f(t)=(a2+b2)2(a2?b2)eatsinbt?2abeatcosbt?+a2+b2bt+2ab?,F(s)=s2((s?a)2+b2)b?(35)f(t)=U(t?c)={01?x<cx?c?,F(s)=se?c?(36)f(t)=g?(t),F(s)=sG(s)?g(0+)[g(0+)means limt?0+?g(t), which is the same as g(0) when g is continuous at 0 .]
(37) f(t)=g??(t),F(s)=s2G(s)?sg(0+)?g?(0+) (38) f(t)=g(n)(t),F(s)=snG(s)?sn?1g(0+)?…?g(n?1)(0?)(39)f(t)=eatg(t),F(s)=G(s?a) (40) f(t)=U(t?c)g(t?c),F(s)=e?csG(s)(41)f(t)=U(t?c)g(t),F(s)=e?cL{g(t+c)}(42)f(t)=?0t?g(u)du,F(s)=sG(s)?(43)f(t)=tg(t),F(s)=?G?(s)(44)f(t)=(?1)ntng(t),F(s)=G(n)(s) (45) f(t)=g?h(t)=?0t?g(t?u)h(u)du,F(s)=G(s)H(s)(46)f(t)=tg(t)?,F(s)=?0??G(u)du